MANAJEMEN USAHA KESEHATAN SEKOLAH DALAM MENINGKATKAN PERILAKU SEHAT SISWA - Saadudin, Idad (Wali Pikir: Journal Of Education, 2023)
The non-optimal healthy behavior of junior high school (SMP) students in West Bandung Regency reflects the limited knowledge and weak attitudes of students in School Health Business Activities (UKS) through the implementation of health education, health services and the implementation of healthy education. The school environment is called TRIAS UKS. This research aims to determine and analyze the application of UKS in improving students’ healthy behavior so that middle school students’ learning effectiveness can be realized. UKS management that is not yet optimal and weak student healthy behavior has an impact on student achievement that is less effective. This research uses a qualitative approach with a case study method. The research results show that the planning of UKS activities in three junior high schools has not been based on the results of analysis of the school environment, both internal and external, as mandated in the central UKS guidelines, so that the planning results do not reflect the picture needed by the school. In organizing UKS coaching, schools try as much as possible to involve all school members, but the implementation is not yet supported by description and task mechanisms and does not refer to management indicators, resulting in overlapping activities. UKS mobilization has not been integrated with other programs so that the implementation of health education, health services and a healthy school environment is still partial. UKS control and supervision has been attempted by each school, but it is still not optimal due to weak control and supervision carried out by the District UKS Advisory Team and in accordance with UKS guidelines. The conclusion of the research generally shows that junior high schools in West Bandung Regency are still in Complete Stratification according to the TRIAS UKS indicator which describes the weak health behavior of junior high school students.